PRIVATISASI ASET PUBLIKSEBAGAI KEBIJAKAN EKONOMI MENURUT KONSEP ALMILKIYAH - Mugiyati Mugiyati (Al Hikmah: Jurnal Studi Keislaman, 2013)
Privatization is the political and economic policies to boost economic growth by way of transfer of economic activities such as the management of public assets were previously managed by the State-Owned Enterprises (SOEs) to private national and foreign, as the country's efforts to improve the welfare of the people. Privatization of public assets is also a condition of the government debt to the International Monetary Fund (IMF) and the World Bank which requires each state to the borrower (debtor) to a policy of structural adjustment programs (structural adjustment programs), in line with global economic trends that wants minimal role of the state in economy was replaced by market mechanisms. Instead, it only provides opportunities privatization to a handful of the bourgeoisie to double the capital and the transfer of control of ownership of public assets from the state to international investors, the impact on the loss of public assets needs of the people, so that is not welfare but impoverishment.Islam has protected the public assets of mastering a handful of people, to ensure the welfare of the entire community, through the ban to have it. Public assets must be managed by the state to be distributed fairly to the well being of the people is not only limited to the three kinds of objects, water, grass and fire only, but includes: First, everything that is needed by the general public that, if not met, could cause divisions and disputes. Second, natural resources are abundant in number so that if controlled by a group of people, would lead to unequal distribution of wealth. Third, natural resources made it impossible nature of its formation is controlled by the individual. Fourth, strategic industries, i.e. industries that produce products/machines required by economy sectors activities such as manufacturing, agriculture, transportation, and telecommunications.